Emerging Therapeutic Strategies for Limbal Stem Cell Deficiency - Ying Dong; Han Peng; Robert M. Lavker (Journal of Ophthalmology)
Identification and characterization of the limbal epithelial stem cells (LESCs) has proven to be a major accomplishment in anterior ocular surface biology. These cells have been shown to be a subpopulation of limbal epithelial basal cells, which serve as the progenitor population of the corneal epithelium. LESCs have been demonstrated to play an important role in maintaining corneal epithelium homeostasis. Many ocular surface diseases, including intrinsic (e.g., Sjogren’s syndrome) or extrinsic (e.g., alkali or thermal burns) insults, which impair LESCs, can lead to limbal stem cell deficiency (LSCD). LSCD is characterized by an overgrowth of conjunctival-derived epithelial cells, corneal neovascularization, and chronic inflammation, eventually leading to blindness. Treatment of LSCD has been challenging, especially in bilateral total LSCD. Recently, advances in LESC research have led to novel therapeutic approaches for treating LSCD, such as transplantation of the cultured limbal epithelium. These novel therapeutic approaches have demonstrated efficacy for ocular surface reconstruction and restoration of vision in patients with LSCD. However, they all have their own limitations. Here, we describe the current status of LSCD treatment and discuss the advantages and disadvantages of the available therapeutic modalities.